Debt financing behaviour: panel data evidence on medium enterprises - Haron, Razali (2015)
Motivated by the recent outstanding growth of Islamic Capital Market (ICM) in Malaysia, this study aims to investigate the debt financing behaviour of Shariah compliant E50 Medium Enterprises (MEs) in Malaysia covering the existence of target debt and the speed of adjustment to target debt from 2009 to 2013. The dynamic model employed and estimated using the Generalized Method of Moment revealed the existence of target debt ratio and firms readjust when deviated. Results also showed inclination to Shariah compliant characteristics of these MEs. This study contributes to the literature and fills the gap by exploring into a relatively new area of debt financing which is the dynamic aspects and also help to enhance the understanding on debt financing behaviour of Shariah compliant MEs in Malaysia ICM.